The use of interactive technology in providing culturally competent care - Kouta, Christiana (My University, 2019)
Transcultural education is a necessity in contemporary world in any science and in combination with multidisciplinary collaboration in research and everyday practice form an asset for the quality of health and life based on human rights. Information technology provides an umbrella framework to liaise professionals, providers, users and quality entities and so on. It plays an important role in health and social professions in utilization of health knowledge and care and in providing transparency and dissemination along with evidence-based decisions for health and social care interventions.
Keywords: culturally competent care; human interactive technology